Evaluation of selection criteria of schools principal in Turkey: A qualitative study in order to define appropriateness of selection criteria of school principal from the point of view of participants - (:unkn) unknown (Sakarya University, 2015)
The purpose of this study is to evaluate the criteria utilized to select school principals from the point of view of participants who participated in principal selection process in Turkey. In this study, the criteria utilized in the selection process of school principal were evaluated by participants who appointed or not appointed at the end of the process as a school principals. A semi-structured interview form was used for data collection and the descriptive analysis was used for analysis of data. The interviews were conducted with 24 participants in the province of Istanbul and Canakkale. They were found that General and Specific Features were found appropriate and sufficient from most participants. Even though, there were slight disagreements among participants regarding appropriateness of criteria of personal features being evaluated, most of the participants thought they were sufficient. The most controversial criteria were award types owned by participants and the points assigned to the awards. Almost all of the participants do not agree upon both the type of the awards and the points assigned to the awards. Another topic of discussion is influence of the interview on result and its content. More than half of the participants emphasized that both impact of the interview on overall result and its content neither fair nor objective. © The Turkish Online Journal of Educational Technology.
Keywords: Criteria evaluation; Evaluation of criteria; Principal selection criteria in Turkey